Global Food Market and International Trade as Market Instrument of Food Resources Redistribution - Stezhko, N.; Стежко, Н. В. (My University, 2016)
The important role of international trade in solving global food problem has been substantiated in the article. A number of challenges in the development of international food trade have been identified, the trends of its dynamics have been defined, the ways of its development related to the need for improving the conditions of trade and its structure, ensuring more favourable conditions of access to the world food market by improving the mechanism of regulation of import tariffs and quotas, export subsidies, internal support measures for producers of food products.
Keywords: global agri-food system; global market; international trade; export of agricultural products; import of agricultural products